The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Le texte de Binnie, Jon. 1995. « Trading places : consumption, sexuality and the production of queer space. » figure dans la bibliographie du cours SOC2014.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques